(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This study aims to examine the implementation of the Project-Based Learning (PBL) model and the Cooperative Learning (CL) model on the understanding of high school students. This study uses a qualitative approach with a focus on literature studies. The data sources that will be used in this study are scientific articles, books, journals, research reports, and other literature sources that are relevant and related to the influence of project-based and cooperative learning models in biology learning. The data analysis method used in this study is literature analysis or systematic literature review. The results of the study showed that both PBL and CL had a positive effect on the understanding of high school students. PBL provides opportunities for students to be actively involved in learning, build deep understanding, and develop critical thinking skills. CL enhances student understanding through interaction and collaboration, facilitates the exchange of understanding, and improves communication and cooperation skills. This research has important implications for educational practice, such as helping teachers choose the right learning model and encouraging the development of teacher training programs on PBL and CL